(untitled) (Bangladesh Journal of Child Health, 2020)
von Willebrand Disease (VWD) is the most common inherited bleeding disorder. It occurs due to either qualitative or quantitative defect of von Willebrand Factor (VWF). VWF is a large multimeric glycoprotein necessary for platelet aggregation and adhesion to the subendothelium following any vascular injury. Typical presentation of VWD patient include mucosal bleeding, easy bruising and bleeding following minor trauma. Rarely, these patients may present with gastro intestinal bleeding. The treatment of choice in mild forms of VWD is the synthetic agent desmopressin. In patients with severe form or in children who do not response to desmopressin, the appropriate treatment is a VWF rich factor VIII concentrate. There are few case reports of VWD with upper gastrointestinal (UGI) bleeding. So, we report a case of 9 years old female child who was admitted at Bangabandhu Sheikh Mujib Medical University in Paediatric Gastroenterology Department with the complaints of recurrent UGI bleeding for 3 years. She also had history of spontaneous gum bleeding, easy bruising, echymosis, prolong bleeding following minor trauma since early age. After appropriate evaluation of the patient including history and relevant investigation, she was diagnosed as a case of VWD with GI bleeding. We report this as it is a rare presentation of VWD. Bangladesh J Child Health 2019; VOL 43 (3) :188-191